The Maqamat of the Rhetorical Word (Despair) in the Qur’anic Discourse - Fayyad, Muhammad Taha (Journal of Tikrit University for Humanities, 2022)
The context in the Qur’anic discourse is uniquely specific, because it bears multiple faces, and it had a great effect in directing the intended meaning, and the station that is one of the non-linguistic elements represented by the circumstances surrounding the text, such as the reasons for descent, the state of the addressee, the subject, the purpose and others. The Qur’anic discourse has many rhetorical methods, which prompted me to choose a topic for my research that is tagged (Maqamat of the word despair in the Qur’anic discourse). And intimidation intended by it many rhetorical purposes; the context had a great role in defining them and revealing their rhetorical secrets.